A case of junctional epidermolysis bullosa intermediate with collagen XVII deficiency treated with dupilumab - Li Zhang; Shangshang Wang; Qinyi Chen; Leihong Xiang (Taylor & Francis Group, 2023)
AbstractInherited epidermolysis bullosa is a heterogeneous group of hereditary skin diseases characterized by skin (mucosa) fragility, which leads to blistering. Junctional epidermolysis bullosa is associated with mutations in genes expressing proteins of the dermo-epidermal junction. Dupilumab, an antibody that directly targets interleukin (IL)-4 receptor alpha, may be an effective treatment for dystrophic epidermolysis bullosa. We describe a case of junctional epidermolysis bullosa that improved with dupilumab.